Acetylation-dependent regulation of PD-L1 nuclear translocation dictates the efficacy of anti-PD-1 immunotherapy - Gao, Yang; Nihira, Naoe Taira; Bu, Xia; Chu, Chen; Zhang, Jinfang; Kolodziejczyk, Aleksandra; Fan, Yizeng; Chan, Ngai Ting; Ma, Leina; Liu, Jing; Wang, Dong; Dai, Xiaoming; et al. (Nature cell biology, 2020)
Immunotherapies that target programmed cell death protein 1 (PD-1) and its ligand PD-L1 as well as cytotoxic T-lymphocyte-associated protein 4 (CTLA4) have shown impressive clinical outcomes for multiple tumours. However, only a subset of patients achieves durable responses, suggesting that the mechanisms of the immune checkpoint pathways are not completely understood. Here, we report that PD-L1 translocates from the plasma membrane into the nucleus through interactions with components of the endocytosis and nucleocytoplasmic transport pathways, regulated by p300-mediated acetylation and HDAC2-dependent deacetylation of PD-L1. Moreover, PD-L1 deficiency leads to compromised expression of multiple immune-response-related genes. Genetically or pharmacologically modulating PD-L1 acetylation blocks its nuclear translocation, reprograms the expression of immune-response-related genes and, as a consequence, enhances the anti-tumour response to PD-1 blockade. Thus, our results reveal an acetylation-dependent regulation of PD-L1 nuclear localization that governs immune-response gene expression, and thereby advocate targeting PD-L1 translocation to enhance the efficacy of PD-1/PD-L1 blockade. Gao et al. uncover p300-induced acetylation and HDAC2-mediated deacetylation of PD-L1, which modulate its nuclear translocation to affect the expression of immune genes and the efficacy of anti-PD-1 therapy.